Environmental correlates of undernutrition among children of 3–6 years of age, Rajkot, Gujarat, India - Zalak Rameshbhai Matariya; Kaushik Kishorbhai Lodhiya; Rajkumar G Mahajan (Journal of Family Medicine and Primary Care, 2016)
Introduction: There are lots of studies focusing on the role of reproductive and child health factors and dietary factors on the nutrition status of the child. The present study is an attempt to highlight the role of macro- and micro-environmental factors in predicting the occurrence of undernutrition in children. Methods: This was a cross-sectional study conducted in field practice area of Community Medicine Department, PDU Medical College, Rajkot. The nutrition status of children was assessed using the weight for age WHO reference standards, 2006. Children below two standard deviation of the reference median (weight for age) were considered as malnourished. Data were collected for sociodemographic factors, sanitation, hygiene, and attitude of mother toward her child, etc., Data were entered in MS excel, and logistic regression was used. Results: Analysis of 495 selected children showed 24% prevalence of undernutrition. Employment status of mothers (adjusted odds ratio [AOR] 1.65), drinking water quality (AOR 1.53), and cleanliness of mother's hands and clothes (AOR 1.91) significantly affected the nutrition status of the child. Children classified in fair or poor category for Briscoe's sanitation scale had 1.34 and1.92 times higher odds of being undernourished (P > 0.05), respectively. Children classified in fair or poor category for Elizabeth's microenvironment scale had 2.05 and 2.41 times higher odds of being undernourished (P < 0.05), respectively. Conclusions: Water, sanitation, and hygiene-related factors, as well as microenvironmental factors, significantly affected the nutrition status of the children.